Effectiveness and Heterogeneous Effects of Purchase Grants for Electric Vehicles - Peter Haan; Adrián Santonja; Aleksandar Zaklan (Environmental and Resource Economics, 2024)
Abstract We evaluate German purchase subsidies for battery electric vehicles (BEVs) and plug-in hybrid electric vehicles (PHEVs) using data on new vehicle registrations in Germany during 2015-2022. We account for confounding time trends and interacting EU-level standards using neighboring countries as a control group. We find that 40% of BEV and 25% of PHEV registrations were subsidy-induced. The program had strong distributional effects, with greater uptake in wealthier and greener counties. We estimate implied abatement costs of 870 euro per ton of for BEVs and 2,470 euro for PHEVs, suggesting that policy makers should re-balance support schemes away from PHEVs.
Additional information: Q54;Q58;H23;R48
Keywords: 330; Decarbonizing road transport; Electric mobility; Purchase subsidies; Policy effectiveness; Distributional effects of climate policy